Toumanian and the Universe - Karaxanyan, L.
Toumanian’s poetic intelligence indeed ignited the universe, ensuring the continuous flow of creation on Earth and into the hearts and minds of people. The rapprochement with the universe represents a cultural endeavor in life organization, aimed at not only rectifying past and present mistakes but also guiding pathways to harmony with the universe and God. His lyrical hero embodies the ultimate human, seamlessly integrated into the universe, reverting to their inherent creator nature and origin. Through this, Toumanian established space as an essential element of identity, a perpetual value. The article explores the connection between Toumanian and space.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture